Waterland: (Re)Textualizing Histories and Historicizing the Past - Duygu SERDAROĞLU (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Graham Swift's novel Waterland (1983) is about Thomas Crick, a history teacher. In his history lessons, Thomas Crick merges public history with his private history as well as local history of Fenlands where he lives, to face and to solve the mysteries of his past. Thus, by intermingling public, private and local histories, he erases all the boundaries between them and hence gives a different understanding/representation of history and also his history lessons become a journey to his past/history within public and local histories although the only reason for him to do so is to give less boring history lessons. In that sense, the novel meets on the same ground with the New Historicism, ourished in the mid-1980s as a “new” approach which challenges the traditional understanding of history as a grand-narrative and which focuses on how history is represented rather than what it represents. This article aims to analyze the novel Waterland which deconstructs and reconstructs the notion of history by focusing on the concepts of memory and time, and thus to elucidate how the novel challenges the traditional appreciation of history as a grand narrative by merging public, local and private histories with multiple representations of history.